Pleiotropic effects of BAFF on the senescence-associated secretome and growth arrest - Rossi, Martina; Anerillas, Carlos; Idda, Maria Laura; Munk, Rachel; Shin, Chang Hoon; Donega, Stefano; Tsitsipatis, Dimitrios; Herman, Allison B; Martindale, Jennifer L; Yang, Xiaoling; Piao, Yulan; Mazan-Mamczarz, Krystyna; et al. (eLife, 2023)
Senescent cells release a variety of cytokines, proteases, and growth factors collectively known as the senescence-associated secretory phenotype (SASP). Sustained SASP contributes to a pattern of chronic inflammation associated with aging and implicated in many age-related diseases. Here, we investigated the expression and function of the immunomodulatory cytokine BAFF (B-cell activating factor; encoded by the TNFSF13B gene), a SASP protein, in multiple senescence models. We first characterized BAFF production across different senescence paradigms, including senescent human diploid fibroblasts (WI-38, IMR-90) and monocytic leukemia cells (THP-1), and tissues of mice induced to undergo senescence. We then identified IRF1 (interferon regulatory factor 1) as a transcription factor required for promoting TNFSF13B mRNA transcription in senescence. We discovered that suppressing BAFF production decreased the senescent phenotype of both fibroblasts and monocyte-like cells, reducing IL6 secretion and SA-β-Gal staining. Importantly, however, the influence of BAFF on the senescence program was cell type-specific: in monocytes, BAFF promoted the early activation of NF-κB and general SASP secretion, while in fibroblasts, BAFF contributed to the production and function of TP53 (p53). We propose that BAFF is elevated across senescence models and is a potential target for senotherapy.